Global Longitudinal Strain (GLS) by 2D speckle tracking echocardiography to predict and diagnose coronary artery disease - Hyder Mejeed Rustum Hussona; Nazar Essa Hasan (Journal of Biomedicine and Biochemistry, 2026)
Background: Non-invasive cardiac imaging is increasingly used nowadays to predict and diagnose structural and functional diseases of coronary arteries with improved efficacy, safety and cost.Objective: To evaluate the ability of two-dimensional (2D) global longitudinal strain (GLS) by speckle echocardiography to predict the presence of significantcoronary artery disease (CAD), disease severity and its’ reproducibility in the stratification of coronary disease risk in suspected patients.Patients and methods: An observational study that was conducted at Al Nasiriya Cardiac Hospital and included 75 patients with suspected CAD who were admitted for elective diagnostic coronary angiography. They divided into 3 groups according to presence of coronary artery stenosis andthe degree of significance. 2D speckle tracking echocardiography was performed for all and its’ ability in the prediction and diagnosis of CAD was studied.Results: Study showed that 60% of patients had significant stenosis, while 30.67% had no stenosis and 9.33% had a non- significant stenosis by coronary angiography. There was a significant variance regarding gender preference and hypertension with no significant variance regarding age,diabetes and smoking status. GLS had significant associations with the degree of coronary stenosis and culprit vessels, having a cut of value of -16.5% for discrimination of significant, non-significant and no stenosis with 83% sensitivity and     84% specificity. GLS had a significant positivecorrelation with the ejection fraction, r = 0.511 at a p-value